Secular Trends in Growth of Preschool Children from Rural Maharashtra, India (Journal of Health, Population and Nutrition, 2013)
The study examined the secular trends in growth of preschool children from rural Maharashtra, India, during 1985-2001. Anthropometric data collected on preschool (